Early postoperative complications in patients operated on for breast cancer using different surgical techniques - A. Kh. Ismagilov; V. E. Karasev (ABV-press, 2021)
Background. Given the steady and intense increase in the incidence of breast cancer, the problem of the development of early complications of reconstructive operations, depending on the characteristics of surgery, remains urgent.Objective: to analyze the characteristics of the early postoperative period in patients operated on for breast cancer using different surgical techniques.Materials and methods. A comparative analysis of clinical examination data was carried out, as well as laboratory and instrumental diagnostic methods for 353 women with stage I to IIIA breast cancer after various surgical treatment options and 40 patients after mammoplasty.Results and conclusions. It has been shown that neither single-step nor delayed reconstructive operations after radical mastectomy increase the incidence of complications in the early postoperative period. Single-step breast reconstruction with the help of an expander can be used in patients with I-IIIA stages of the tumor process.